Azure Serverless Computing Cookbook : Build and Monitor Azure Applications Hosted on Serverless Architecture Using Azure Functions, 2nd Edition. - Sreeram, Praveen Kumar (Packt Publishing Ltd, 2018)
Microsoft provides a solution to easily run small segment of code in the Cloud with Azure Functions. Azure Functions provides solutions for processing data, integrating systems, and building simple APIs and microservices. This recipe-based guide will help you gain all the skills required to work with serverless code architecture and providing ...